Balancing food security, vertebrate biodiversity, and healthy rice agroecosystems in Southeast Asia - Propper, Catherine R.; Sedlock, Jodi L.; Smedley, Richard E.; Frith, Oliver; Shuman-Goodier, Molly E.; Grajal-Puche, Alejandro; Stuart, Alexander M.; Singleton, Grant R. (Elsevier, 2024)
Rice is the dominant food staple and an important economic resource throughout Asia. Lowland rice production also provides important wetland habitats in support of biodiversity that may provide ecosystem services back to the rice agroecosystems. This review summarizes the literature on the ecosystem benefits that amphibians, birds, bats, and rodents support in the context of the Southeast Asia rice agroecosystems. The literature provides evidence that these taxonomic groups contribute to cultural, regulatory, and provisioning services in support of smallholder farmers and may allow for economic benefits through reduced use of chemical inputs into crops. We encourage a multipronged research approach to bring stakeholders together to provide structured and scalable education programs that will lead to improved human and agroecosystem health through the promotion of understanding the positive feedbacks from biodiversity in these important agricultural wetland habitats.